PENGARUH PENGGUNAAN MODEL PEMBELAJARAN RODA KEBERUNTUNGAN TERHADAP MOTIVASI BELAJAR PPKn SISWA DI SMP NEGERI 1 BENAI KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Nursantipa, Nursantipa; Erlinda, Sri; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is based on the low motivation of learning PPKn of the students at SMP Negeri 1 Benai. The formulation of the problem in this research is "Is there any significant effect of using Wheel of Fortune learning model toward students’ motivation in learning PPKn at SMP Negeri 1 Benai Kecamatan Benai Kabupaten Kuantan Singing ?". This study aims to determine the effect of using Wheel of Fortune learning model toward students’ motivation in learning PPKn at SMP Negeri 1 Benai Kecamatan Benai Kabupaten Kuantan Singingi. This research was conducted at SMP Negeri 1 Benai in February 2018. This research was a quantitative descriptive which is experimental research which the students of grade VIII SMP Negeri 1 Benai became the population in this study. The sample in this research was taken based on "Random Sampling" technique. Where the class taken into the sample was students of class VIII.a (experimental class) given the learning model of Wheel of Fortune, and class VIII.c (control class) were students who were given the conventional method. Then data analysis by using homogeneity test and "t" test. Based on the result of research indicated that there was an effect of learning motivation between student who using Wheel of Fortune learning model and conventional method in SMP Negeri 1 Benai ( > ). Where there was an average increase toward motivation in learning PPKn of experimental class from 19.8 to 27 and the average of PPKn learning motivation of control class from 21,5 to 19,30. Thus the hypothesis which reads that there is an effect of using Wheel of Fortune learning model toward students’ motivation in learning PPKn at SMP Negeri 1 Benai Kecamatan Benai Kabupaten Kuantan Singingi, can be accepted.Keywords: Wheel of Fortune, Learning Motivation PPKn